Educational Transition in Self-Directed Learning amongst Selected Adult Distance Learners of Universiti Putra Malaysia - Wan Ismail, Wan Zawawi (2007)
The need to change and employ the necessary learning skills are essential for successful learning considering their other responsibilities in life which is part and parcel of being an adult learner. One solution is for the adult learners to undergo an educational transition from the earlier mindset to the needs of the current environment and to be self-directed in their learning thus assuming the responsibility for their own learning by building and employing the necessary skills to deliver the desired results in learning. This study examined the educational transition in self-directed learning by looking at the respondents’ prior beliefs, the phases that they went through as adult distance-learners at the Universiti Putra Malaysia. The study was guided by three research questions: (1) What were the learners’ prior beliefs about learning? (2) How do adult distance-learners experience the phases of self-directed learning? and (3) How do they employ self-directed learning as adult distance-learners? A qualitative research design was employed for this study which was deemed appropriate, given the research questions which were to obtain a view into the respondents’ life-worlds and to understand their personal meanings constructed from their life experiences. Data were primarily gathered through interviews on six selected respondents based on the criteria set by the researcher. Three conclusions were drawn from this study. First, adult learners do have a set of beliefs which are; learning would change their lives, mode of teaching and learning and also on their ability to face the challenges prior to their engagement as adult distance-learners at the Universiti Putra Malaysia. Second, adult distance-learners went through five different phases of learning to be self-directed which includes the phases of disorientation, exploration, transformation, adaptation before they are able to come to terms with learning as distance-learners or the reconciliation phase. Third, after going through the phases of learning, adult distance-learners do employ self-directed learning skills in their learning. The employment of skills such as personal diagnosis, communicative, resource identification and time management had helped adult distance-learners in their transition from being recipients to pursuers, seekers and creators of knowledge in a distance learning environment thus enhancing the successful completion o their learning endeavor.